Technologies, Ethics and Journalism’s Relationship with the Public - Duncan, Megan (2020)
Drones can provide a bird’s eye view of breaking news and events that can be streamed live or used in edited news coverage. Past research has focused on the training and ethics of journalists and drone operators. Little attention, however, has been given to audiences and their acceptance and perception of ethics. We suggest that audiences who are open to personal technology use will perceive news media using unmanned aerial vehicles (UAVs) as more ethical in an extension of the Diffusion of Innovation Theory. In a survey (N = 548) of adults living in the United States, we explore the correlates between trust, technology, privacy, and the use of UAVs. Results suggest all three are positively correlated with openness toward drone journalism. We find the audience has preferences for the types of news stories that should be covered using drones. Participants indicated they welcome drone journalism when covering traffic and investigative stories, but not celebrities and politicians. The findings have implications for newsrooms, suggesting transparency and outreach to educate people on the technology could help build trust. Further, the results suggest that Diffusion of Innovation theory can be applied when mediated through news media.